IMPLEMENTATION OF GUIDED INQUIRY IN COORDINATION SYSTEM MATERIAL TO IMPROVE SCIENCE PROCESS SKILL AT CLASS XI IPA 3 STUDENTS IN SMA BATIK 2 SURAKARTA IN ACADEMIC YEAR 2013/2014 - Marjono, Idhun Prasetyo R, Baskoro A P (P Biologi FKIP UNS Surakarta, 2015)
This research aimed to improve science process skill in coordination system material of Biology subject at XI IPA 3 Class SMA Batik 2 Surakarta with implementation of Guided Inquiry. This research is a Classroom Action Research which was done in two cycles. Each cycle consists of 4 steps, those are: planning, acting, observation, and reflection. The technique of data collection used questionaire, observation sheet, test, and interview. Validity used triangulation method, while data analysis used descriptive analysis. The results of this research showed that implementing classroom research by using guided inquiry could improve students? science process skill in Biology subject, matched with second cycle target. The percentage of achievement aspect in science process skill at pre-test was low because the teaching and learning was dominated by teaching centered. While the average percentage of achievement aspect in science process skill in accordance with the observation sheet in first cycle was 53,29% and second cycle was 77,68% (increased 24,39%), average of achievement in first cycle was 56,1 % and second cycle was 78,35% (increased 22,25%). Therefore, implementation of teaching technique by using guided inquiry could stimulate students and force them to be more active in Biology subject. Based on the research result above, it can be concluded that the implementation of guided inquiry in coordination system material of Biology subject can improve science process skill of students at class XI IPA 3 SMA Batik 2 Surakarta in academic year 2013/ 2014. Keywords: Guided Inquiry, Science Process Skill